The Impact of Urban Sprawl on the Socioeconomic Conditions of the Population in Tamanan Village, Indonesia - Sri Rum Giyarsih (Faculty of Geography, Universitas Gadjah Mada, 2023)
This study aimed to analyse the impact of urban sprawl on the (1) social, (2) economic, and (3) technological conditions of the population in Tamanan Village, on the outskirts of Yogyakarta City. For data collection, this survey research employed structured interviews with 40 respondents selected through multistage random sampling. It also used complementary in-depth interviews with seven (7) purposively sampled key informants to deepen the analysis. The answers from the structured interviews were analysed with descriptive statistics in the form of single-frequency tables, while the data derived from the in-depth interviews were processed using a qualitative descriptive approach. The results show that the impact of urban sprawl on the social (37.5%) and economic conditions (40%) was mostly high, while the effect on the technological conditions of the population in the study area fell mainly under the medium category (47.5%). In conclusion, the phenomenon of urban sprawl in the study area has affected the social, economic, and technological conditions of the population.